2020
DOI: 10.1186/s42836-020-00045-5
|View full text |Cite
|
Sign up to set email alerts
|

Resurfacing hemiarthroplasty versus stemmed hemiarthroplasty for glenohumeral osteoarthritis: a meta-analysis

Abstract: Background: Though total shoulder arthroplasty (TSA) has been an acknowledged treatment option for glenohumeral osteoarthritis, resurfacing hemiarthroplasty (RHA) and stemmed hemiarthroplasty (SHA) may be preferred in some circumstances by surgeons, especially for treating young or active patients. However, decision-making between the RHA and SHA is controversial. Therefore, we conducted a meta-analysis to systematically compare two surgical procedures in terms of postoperative functional outcomes, range of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…A recent meta-analysis of case series and cohort studies demonstrated similar shoulder scores and a higher revision rate in the resurfacing group. 13 The duration of follow-up was mixed, and the loss to follow-up was unclear. In the National Joint Registry of England Wales and Northern Ireland, the stemless hemiarthroplasty may have the greatest revision rate compared to resurfacing or stemmed replacements at 5 years across all ages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent meta-analysis of case series and cohort studies demonstrated similar shoulder scores and a higher revision rate in the resurfacing group. 13 The duration of follow-up was mixed, and the loss to follow-up was unclear. In the National Joint Registry of England Wales and Northern Ireland, the stemless hemiarthroplasty may have the greatest revision rate compared to resurfacing or stemmed replacements at 5 years across all ages.…”
Section: Discussionmentioning
confidence: 99%
“…These may have a lower risk of revision compared to stemless and resurfacing implants, however current reports are inconclusive. 12 , 13 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shoulder hemiarthroplasty (HA) involves only the replacement of the humeral articular surface and is performed when glenoid resurfacing is contraindicated due to poor glenoid bone stock or in other selected cases [ 72 , 73 ]. Resurfacing hemiarthroplasty (RHA) has alternatively been proposed in an attempt to restore joint congruency while conserving proximal humeral bone stock and native anatomy of glenohumeral articulation [ 74 ]. Cuff-tear arthropathy of the shoulder has proved itself as a complex and difficult-to-treat form of shoulder degeneration associated with a massive chronic tear or other form of rotator cuff insufficiency that manifests as proximal migration of the humerus and erosion of the superior part of glenoid.…”
Section: Replacementmentioning
confidence: 99%